AN ANALYSIS OF USING SLANG LANGUAGE OF GEN Z BASED ON TIKTOK VIDEOS: SOCIOLINGUISTICS APPROACH - Amelia Domu Romauli Siagian; Nenni Triana Sinaga; Febrika Dwi Lestari (J-Shelves of Indragiri (JSI), 2024)
Slang languagehas become part of everyday language, as people use it in daily conversations. The use of slang is more dominant among young people, especially Gen Z. Generation Z has a big influence in the spread of slang, especially on various social media today, one of which is currently popular is TikTok.Slang is a relaxed language that is often used by people in daily conversations in various fields. However, the existence of this slang also creates problems in the language structure. Slang may initially only be used in certain environments, but some can develop into part of a wider language in today's culture and trends. Slang often creates or changes the meaning of words or phrases that already exist in formal language.This research aims to find out the type of slang used by Gen Z based on TikTok videos (Partridge: 2004) and identify the dominant type of slang used by Gen Z based on TikTok videos.This researchusesa Descriptive Qualitative method by selecting and collecting data from TikTok Videos.From the data analyzed, there are 25 data types of Society slang such as mukbang, viral, massage, worth it, guys, burn out, fomo, healing, friendly, idol, pov, pick me girl, cool cats, kittens, guys, gonna, kicking off, gross, darn it, guys, very dead, bts, shades, a little doll, 4 data types of slang in Publicity such as Reglow, Frestea, Fresh Break Zone, Everwhite, and last 1 data type of PublicHouse slang that is cheering. From the analysis of calculating percentage data, Society slang with a percentage result of 83,33%, slang in Publicity 13,33%, and Public House slang gets 3,33%. From these findings, it is concluded that Society slang is the most dominant type of slang among other types of slang.